The Agonism Between Democracy and Sovereignty as the Form of the Political - Lambropoulos, Vassilis (Stasis, 2018)
Book Review: Dimitris Vardoulakis, Stasis Before the State: Nine Theses On Agonistic Democracy New York: Fordham University Press, 2018, 153 pp., ISBN 9780823277407